Log odds of positive lymph nodes is a better prognostic factor for oesophageal signet ring cell carcinoma than N stage - Wang, Feng (World J Clin Cases, 2021)
BACKGROUND: Signet ring cell carcinoma is a rare type of oesophageal cancer, and we hypothesized that log odds of positive lymph nodes (LODDS) is a better prognostic factor for oesophageal signet ring cell carcinoma. AIM: To explore a novel prognostic factor for oesophageal signet ring cell carcinoma by comparing two lymph node-related prognostic factors, log odds of positive LODDS and N stage. METHODS: A total of 259 cases of oesophageal signet ring cell carcinoma after oesopha-gectomy were obtained from the Surveillance, Epidemiology, and End Results database between 2006 and 2016. The prognostic value of LODDS and N stage for oesophageal signet ring cell carcinoma was evaluated by univariate and multivariate analyses. The Akaike information criterion and Harrell’s C-index were used to assess the value of two prediction models based on lymph nodes. External validation was performed to further confirm the conclusion. RESULTS: The 5-year cancer-specific survival (CSS) and 5-year overall survival (OS) rates of all the cases were 41.3% and 27.0%, respectively. The Kaplan-Meier method showed that LODDS had a higher score of log rank chi-squared (OS: 46.162, CSS: 41.178) than N stage (OS: 36.215, CSS: 31.583). Univariate analyses showed that insurance, race, T stage, M stage, TNM stage, radiation therapy, N stage, and LODDS were potential prognostic factors for OS (P < 0.1). The multivariate Cox regression model showed that LODDS was an significant independent prognostic factor for oesophageal signet ring carcinoma patients after surgical resection (P < 0.05), while N stage was not considered to be a significant prognostic factor (P = 0.122). Model 2 (LODDS) had a higher degree of discrimination and fit than Model 1 (N stage) (LODDS vs N stage, Harell’s C-index 0.673 vs 0.656, P < 0.001; Akaike information criterion 1688.824 vs 1697.519, P < 0.001). The results of external validation were consistent with those in the study cohort. CONCLUSION: LODDS is a superior prognostic factor to N stage for patients with oesophageal signet ring cell carcinoma after oesophagectomy.